2020
DOI: 10.3390/nu13010121
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perception of Food Insecurity and of Its Effects on Their Children in Italy Six Months after the COVID-19 Pandemic Outbreak

Abstract: The Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) pandemic and subsequent containment measures are causing an increase in food insecurity (FI) worldwide, with direct consequences on children’s nutrition. We aimed to investigate the effects of the lockdown imposed in Italy on FI and changes in eating habits and body weight in the pediatric population 6 months after the beginning of the pandemic through a cross-sectional online survey proposed to parents of children <18 and living in Italy. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 68 publications
4
54
0
3
Order By: Relevance
“…12 Finally, the lack of the school day likely led to variable and later sleep schedules, both of which have been linked to increased risk for overweight or obesity. 58,59 Preliminary and largely self-reported evidence from around the world indicates that during the pandemic, children were more sedentary, engaged in more screen time 39 and less physical activity, 13,40,41 ate more unhealthy and fewer healthy foods, 13,42 and experienced later and more variable sleep schedules. 43,44 Engagement in similar behaviors is likely the behavioral mechanism responsible for the accelerated BMI gain in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Finally, the lack of the school day likely led to variable and later sleep schedules, both of which have been linked to increased risk for overweight or obesity. 58,59 Preliminary and largely self-reported evidence from around the world indicates that during the pandemic, children were more sedentary, engaged in more screen time 39 and less physical activity, 13,40,41 ate more unhealthy and fewer healthy foods, 13,42 and experienced later and more variable sleep schedules. 43,44 Engagement in similar behaviors is likely the behavioral mechanism responsible for the accelerated BMI gain in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary and largely self-reported evidence from around the world indicates that during the pandemic, children were more sedentary, engaged in more screen time 35 and less physical activity, 9 , 36 , 37 ate more unhealthy and fewer healthy foods, 9 , 38 and experienced later and more variable sleep schedules. 39 , 40 Engagement in similar behaviors is likely the behavioral mechanism responsible for the accelerated BMI gain in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying modifiable factors associated with FI can serve as a basis for designing strategies that mitigate the consequences of disruptions caused by health crises, such as the pandemic and the consequent FI, and that strengthen regional food systems, making them more sustainable and sustainable. Although several studies have evaluated FI during the pandemic, the majority correspond to high- or low-income countries with socioeconomic and cultural characteristics that do not allow comparisons with our continent 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 . In LAC, studies in Brazil, Mexico, and Peru have been published 21 , 22 , 23 : however, these have been carried out in small samples and did not evaluate the influence of different sociodemographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, higher food prices, changes in diets, increased depression, anxiety and physical violence against women have all been associated with stay-at-home orders. (11,12,13) Recent studies have also reported an increase in food insecurity after implementation of stay-athome orders, (14)(15)(16) which worsens as the crisis intensifies. (11) These results are alarming, especially considering that the World Food Program estimated the number of people experiencing food insecurity will increase to 265 million by the end of 2020, (17) accompanied by potential negative effects on health and household relations.…”
Section: Introductionmentioning
confidence: 99%